2017
DOI: 10.1088/2057-1976/aa56f2
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures, concentrations and energies: an ideal equation to extend therapeutic efficiency on radioresistant 9L tumor cells using ${{\rm{Ta}}}_{2}{{\rm{O}}}_{5}$ ceramic nanostructured particles

Abstract: This work presents an in-depth analysis into the dependencies of radiosensitisation on x-ray beam energy, particle morphology and particle concentration for Ta O 2 5 nanostructured particles (NSPs). A maximum sensitisation enhancement ratio of 1.46 was attained with irradiation of a 10 MV x-ray photon beam on 9L cells exposed to the less aggregated form of NSPs at 500μg ml −1 . A significant increase in sensitisation of 30% was noted at 150 kVp for irradiation of the less aggregated form of tantalum pentoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Subsequently, it was shown that tantalum pentoxide nanoceramics/ceramic nanostructured particles (Ta 2 O 5 NSPs) exposed to MV X-ray photons could promote an obvious radiation dose enhancement in 9L glioma cells 165 . Several relevant follow-up studies concerning Ta 2 O 5 NSP radiosensitization have been published 166 - 169 . Considering the lower oxygen partial pressure (pO 2 ) inside tumors and advantages of multifunctional nanotheranostics, a series of modified and functionalized tantalum oxide nanoparticles (TaOx NPs) have been synthesized, and their diagnostic and therapeutic application in radiotherapy has been demonstrated 170 - 173 .…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…Subsequently, it was shown that tantalum pentoxide nanoceramics/ceramic nanostructured particles (Ta 2 O 5 NSPs) exposed to MV X-ray photons could promote an obvious radiation dose enhancement in 9L glioma cells 165 . Several relevant follow-up studies concerning Ta 2 O 5 NSP radiosensitization have been published 166 - 169 . Considering the lower oxygen partial pressure (pO 2 ) inside tumors and advantages of multifunctional nanotheranostics, a series of modified and functionalized tantalum oxide nanoparticles (TaOx NPs) have been synthesized, and their diagnostic and therapeutic application in radiotherapy has been demonstrated 170 - 173 .…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…Selected doses (1, 2, 3, 5 and 8 Gy) were delivered at the cell level in single fraction at room temperature and in full scatter conditions, with dose-rates of 0.7 and 5 Gy min −1 for kilovoltage and megavoltage experiments respectively. This difference in dose rates has been shown by Oktaria et al (2017) to have insignificant effect on the survival of 9L cells. Moreover, the selected radiation energies have similar RBE on 9L surviving fraction.…”
Section: Irradiation Procedures and Set Upmentioning
confidence: 77%
“…The use of tantalum pentoxide-nanostructured particles (Ta 2 O 5 NSPs) is currently being studied as a radiation sensitiser based on its high-mass energy absorption coefficient, and is novel in the field of nanomedicine. Ta 2 O 5 NSPs have been experimentally shown to cause cell sensitisation in a higher energy MV radiation field (Brown et al 2017). This study found that when the 9L cells containing Ta 2 O 5 NSPs exposed to the radiation, a higher degree of damage (due to dose enhancement) is observed in comparison to the irradiated cells that were not treated by the Ta 2 O 5 NSPs.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The signal enhancement effect shown in this paper is expected to occur for all high‐Z materials as the photoelectric cross section is larger for high‐Z material but its magnitude is dependent on the atomic number Z with respect to the reference low‐Z material. We selected tantalum (Ta) and aluminum (Al) in this study by way of example and because of the recent interest in the fabrication of Tantalum‐based nanoparticles as radiosensitizers for tumor treatments . Furthermore, the dose enhancement caused by tantalum stents have been investigated via Monte Carlo simulation for intravascular brachytherapy but not measured directly.…”
Section: Introductionmentioning
confidence: 99%